2002
DOI: 10.1590/s1413-78522002000300004
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of lumbar vertebral pedicle and adjacent neural structures

Abstract: RESUMOPara avaliação da morfometria do pedículo vertebral lombar e sua relação com as estruturas neurais, foram dissecados 14 cadáveres do sexo masculino, adultos, onde foram avaliados o tamanho do pedículo vertebral lombar, através da mensuração do seu diâmetro longitudinal e transversal. Os dados obtidos mostraram aumento do pedículo de L2 a L5, tanto no diâmetro longitudinal quanto transversal, sendo o primeiro maior. A relação do pedículo lombar com as estruturas neurais, foram avaliadas através da mensura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Measurement directly from plain AP radiographs are almost same as measured from computerized tomographs and from even the lumbar vertebrae [5]. The present study was done on the lumbar vertebral pedicles to give the average dimensions of the pedicles which will serve as the reference for the choice of sizes of screw for trans pedicular screw fixation [6]. Preoperative determination of especially the horizontal diameter of the pedicles to be used for screw implantation from standardized Anteroposterior X-rays is the easiest way to avoid complication [7].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement directly from plain AP radiographs are almost same as measured from computerized tomographs and from even the lumbar vertebrae [5]. The present study was done on the lumbar vertebral pedicles to give the average dimensions of the pedicles which will serve as the reference for the choice of sizes of screw for trans pedicular screw fixation [6]. Preoperative determination of especially the horizontal diameter of the pedicles to be used for screw implantation from standardized Anteroposterior X-rays is the easiest way to avoid complication [7].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the L1 and L2 was statistically significant (p = 0.0067), the same was true for L2 and L3 (p = 0.0017), L3 and L4 (p < 0.0001), L4 and L5 (p = 0.0238) using paired "t" test. Literature reveals that lumbar pedicle screws in circulation have their diameters ranging from 5.0 mm to 7.5 mm [3]. Since the minimum diameter in the present study is 9.24 on the left side at L2 vertebral level, lumbar pedicles could receive the pedicle screws in circulation.…”
Section: Discussionmentioning
confidence: 54%
“…These imply that the more distal lumbar vertebral pedicles could safely receive larger diameter pedicular screws. Matuoka and Júnior [3] reported that the lumbar pedicular screws in circulation have a diameter ranging from 5.0 mm to 7.5 mm. Therefore, we agree that the lumbar vertebral pedicle in circulation can be safely introduced in surgical procedures as the minimum average diameter recorded in this study was Karkhyle et al [10] of Chinese Singaporeans and Maharahtarian populations respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNRs were measured in relation to the pedicles, DRGs, and spinal cord using modified descriptions from two previously published studies (Matuoka & Basile Júnior, 2002;Mirkovic et al, 1995) and these measurements are demonstrated in Figure 1a • Position C (extra-foraminal): the area bordered medially by the lateral edge of the caudal pedicle.…”
Section: Measurementsmentioning
confidence: 99%